KEBIJAKAN KEIMIGRASIAN DALAM PENAHANAN PENDEPORTASIAN DETENI PADA MASA COVID-19 - Nuraeni, Dita Ayu (Polteknik Imigrasi, 2023)
This research focuses on discussing the trapping of detainees who had carried out the deportation process during the Covid-19 period. There is a policy provided by Immigration Officers through the Government of Indonesia and in collaboration with the Ministry of Foreign Affairs, using qualitative research methods where data searches are obtained from document literature, official websites and several journals and even articles, this research finally got a result, namely when during the covid-19 period When this happens, the government does not only focus on health but also the entry and exit gates for foreign nationals. When that happens, of course there are several foreign nationals who are already in Indonesian territory, not only in the interests of work and travel, there are also cases of criminal acts that endanger the stability of national security. Immigration acts by transferring the foreigner to the detention center as a temporary detention center awaiting the deportation process. When deportation occurs, these former detainees are not immediately released by immigration, but they have to report regularly to immigration because they are still in the territory of Indonesia which was attacked by the epidemic, with this of course the detainees get a temporary residence permit by immigration for a specified period while waiting immediate deportation When the epidemic conditions began to improve.